The Falcon Throne - Miller, Karen, 1961- (London Orbit, 2014)
A royal child, believed dead, sets his eyes on regaining his father's stolen throne. A bastard lord, uprising against his tyrant cousin, sheds more blood than he bargained for. A duke's widow, defending her daughter, defies the ambitious lord who'd control them both. And two brothers, divided by ambition, will learn the true meaning of treachery. All of this will come to pass, and the only certainty is that nothing will remain as it once was.
Keywords: Inheritance and succession -- Fathers and sons -- Illegitimacy